Transcriptome analysis of Ipomoea cairica algicidal mechanism against Phaeocystis globosa - Liang, Dayong; Li, Huanxin; Pan, Yuxuan; Liu, Zihan; Xiang, Hua (Frontiers in Marine Science, 2025)
Phaeocystis globosa is a globally distributed harmful algal bloom species that causes severe damage to local environments and economies. The use of the invasive plant Ipomoea cairica as an algaecide for P. globosa is an environmentally friendly management strategy. Although previous studies have found that I. cairica extracts can effectively inhibit P. globosa growth, the molecular mechanism of cellular response to this algaecide remains unclear. Therefore, transcriptome differences between 24 and 48 h after treatment with I. cairica extracts were investigated to explore the P. globosa gene expression changes in response to the algaecide. In this study, control groups were treated with sterile seawater, while experimental groups were exposed to I. cairica extracts (final concentration of 1%). The results of physiological experiments showed no difference in the number of solitary cells and colonies at 24 h, but significant decreases at 48 h. Transcriptomic data also showed significant differences in differentially expressed genes (DEGs) at 24 and 48 h. DEGs were mainly upregulated at 24 h and downregulated at 48 h. Mitogen-activated protein kinase (MAPK) and phosphatidylinositol (PI) signaling pathways that respond stress in the external environment were activated throughout the response process. Genes related to the antioxidant enzyme system and autophagy were upregulated at 24 h, which may contribute to the stress response mechanisms of P. globosa. Downregulation of photosynthesis-related genes leading to inhibition of the photosynthetic system and thus accelerating the accumulation of reactive oxygen species (ROS) may be responsible for the eventual cell death. In addition, 411 known compounds were identified usingultra-high-performance liquid chromatography (UHPLC). Unfortunately, apigenin-7-O-glucoside, a flavonoid, did not have a significant inhibitory effect on P. globosa. This study highlights the mechanism of the toxic effect of I. cairica extracts on P. globosa and provides a theoretical basis for the development of an algaecide targeting P. globosa.